Worldwide prevalence of obesity among firefighters: a systematic review protocol - Edgard Melo Keene Von Koenig Soares; Denise Smith; Luiz Guilherme Grossi Porto (BMJ Open)
Introduction Obesity may interfere with job performance and increase the risk of injury during firefighting activity. Obesity also has many deleterious effects on health indices and is associated with higher all-cause mortality. Studies report a high prevalence of obesity in the fire service. Also, firefighters’ work schedule (12-hour to 24-hour shifts) and food availability during night shifts may be related to weight gain. Studies in American firefighters have shown annual weight gain between 0.5 and 1.5 kg. This study aims to report the obesity prevalence in the fire service to describe how it varies based on country and region, job status, type of firefighter and gender.Methods and analysis The main outcome evaluated will be obesity prevalence. We will systematically search the literature databases PubMed, Medline, Web of Science, Sportdiscus, Academic Search Premier, Cumulative Index of Nursing and Allied Health Literature (CINAHL), SciTech Premium Collection, Sports Medicine & Education Index, Research Library and Scopus. One reviewer will perform the search. Two independent reviewers will select studies, extract data from eligible studies and evaluate their methodological and reporting quality. Agreement between reviewers will be measured using Cohen’s kappa. Other data of interest will include age, body mass index, body fat percentage, job status (career, volunteer or military), years of service and type of firefighter (eg, structural and wildland firefighter). We will produce a narrative summary of our findings. Tables will be generated to summarise data.Ethics and dissemination This systematic review does not require ethics clearance since published studies with non-identifiable data will be used. The results of the systematic review will be disseminated via publication in a peer-reviewed journal and through conference presentations.PROSPERO registration number CRD42019129122.